Agri-food trade trends in Papua New Guinea: Reflections on COVID-19 policies and dietary change - Schmidt, Emily; Fang, Peixun (International Food Policy Research Institute, 2020)
The onset of the COVID-19 pandemic has presented a unique challenge to governments across the globe, reinforcing the need to improve understanding of domestic and international trade trends to provide more informed options for policy response. Papua New Guinea’s growing international trade in food and other agricultural products will continue to be important to overall food security outcomes among rural and urban households in the country. Rural households that produce key export cash-crops, such as coffee, cocoa, or palm oil, depend on the cash economy to supplement their food consumption, while urban households depend on rice and other agri-food imports, as well as domestic goods, for consumption. This project note focuses on trends in agrifood imports and exports during the last two decades to better evaluate potential changes in import demand and export potential for PNG. In doing so, it informs an upcoming economy-wide multi-market model analysis that will evaluate a variety of potential shocks to PNG’s agri-food system on household welfare in order to identify policies to manage potential food security threats. The COVID-19 pandemic is one of many diverse shocks that may adversely affect the economy of PNG over the next decade. The expansion of a portfolio of organized databases, analytical tools, and policy resources, such as the multimarket model, is warranted to facilitate real-time policy analyses to inform key development investments and initiatives.